WORKSHOP PEMANFAATAN PLATFORM AI UNTUK MEMBUAT MEDIA AJAR PJOK BERBASIS MULTIMEDIA INTERAKTIF - Butsiarah Butsiarah; Bahrul Alim; Fatoni Fatoni; Ahmad Yani; Andi Saiful Alimsyah (LPPM Institut Pendidikan Nusantara Global, 2026)
This community service activity aimed to improve the competence of university students as prospective Physical Education, Sports, and Health (PJOK) teachers in utilizing Artificial Intelligence (AI) platforms to develop interactive multimedia-based teaching media. The workshop was conducted through training sessions, hands-on practice, and mentoring in the creation of innovative digital learning media adaptable to current educational technology developments. The participants consisted of university students as prospective PJOK teachers who were introduced to the use of various AI platforms to produce learning materials such as interactive videos, presentations, digital quizzes, and engaging visual learning designs. The results showed that the workshop successfully enhanced participants’ knowledge and skills in integrating AI technology into the PJOK learning process. In addition, participants demonstrated high enthusiasm and were able to create teaching media products that were more creative, interactive, and effective in supporting learning activities. This activity is expected to encourage more innovative PJOK learning transformation and improve the quality of education in the digital era.